Special Concrete and Composites 2017 : selected, peer reviewed papers from the 14th International Conference, Special Concrete and Composites 2017, October 10-11, 2017, Skalský Dvůr, Czech Republic - Reiterman, Pavel (Key engineering materials ;, 2018)
The 14th International Conference "Special Concrete and Composites" (October 10-11, 2017, Skalský Dvůr, Czech Republic) was focused on the problems of preparing and use of the special concretes and composites in the practice of the contemporary construction. We hope that published results will be useful for many specialists from the area of building materials and concrete structures. Using of special concretes and composites is often closely connected with severe loading conditions of final elements. Design and development of the mentioned materials must take account of basic properties of all components because they can be special by their binder system, used fillers or by other technological solutions. Concrete, Cement Based Composites, Cement Supplementary Materials, Binder Systems, Concrete in Severe Conditions Materials Science.